Komunikasi Pemasaran Wisata Taman Okura Dalam Upaya Meningkatkan Keputusan Berkunjung Wisatawan - Adek Muhayat Saputra; Rumyeni Rumyeni (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze how Okura tourist park marketing communications in an effort to increase tourists' visiting decisions. The method used in this research is a qualitative method to produce descriptive data with data collection techniques in the form of interviews, observation and documentation. Based on the research results, it was found that Okura Tourism Park has implemented various marketing communications to increase tourists' visiting decisions. Internet marketing is divided into social media marketing & websites, internet marketing has a big impact in attracting a wide range of visitors, social media marketing uses Instagram, Facebook, TikTok. Sales promotion is simply done by giving discounts to camping land renters and reducing the price of visiting tickets, which has an impact on attracting visitors, but its implementation cannot be done sustainably and is not well publicized. Public relations & publicity is carried out by carrying out event activities with the community and establishing relationships with external parties, and utilizing mass media and journalists who come to cover tourism for news so that it can have a significant influence in increasing visiting decisions.